Confronting Fiji Futures - Haroon Akram-Lodhi, A. (ANU Press, 2016)
Fiji, post-independence, has seen several governments, two military coups and, amidst sweeping social, economic and political changes, the presence of divisive identity politics in its journey towards a united, collective Fiji community. This republished edition of Confronting Fiji Futures takes in these landmark events and eventualities, and aims at a forward-looking assessment of the realities facing Fiji in the present and the future. It focuses on the period of the coups up to and including the 1999 general elections, when an explicitly multiethnic party won government in a surprise landslide result. This book is the result of a collaborative research project based at the Institute of Social Studies, The Hague, in the Netherlands - an institution with a long tradition of collaborative teaching, research and advisory services in the South Pacific region. It aims to present a range of relevant issues from a number of vantage points. It has brought together a strong diversity of authors led by A. Haroon Akram-Lodhi, including John Cameron, Ganesh Chand, Martin Doornbos, Yash Ghai, Holger Korth, Sunil Kumar, Biman Prasad, Jacqueline Leckie, Satendra Prasad, Steve Ratuva, Robbie Robertson, Ardeshir Sepehri and William Sutherland.